(3MdjI GdeMGVQI aj UfGYI GdTYQ hCfhGYgs - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s ((3EHQGgje Hf eMeO GdTgjQ HGdhRjQ s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg YR hLd hGdUdGI Ydi QShdg Bdg aEf CTQa GdcdGe eG Sgd SHjdg hbQH eCNPg hHYO eQGeg hGYJOdJ CbSGeg hQbJ MhGTjg s
(3BNQgG (B:s
(3cUOY GdRLGLI eG JSJWj` Y ca GdUfGY dg Cf JMjQG s
(3GdUaMI GdChdi HNW MOjKs
(3HQSe GdNRGfI GdgGTejI GdYdhjI dCejQ GdeDefjf CMeOs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B56s
Keywords: (3GdCOHs